American Literatures Prior to 1865 - Peterson, Scott D. (Open textbook library., 2022)
This work was created as part of the University Libraries’ Open Educational Resources Initiative at the University of Missouri–St. Louis. A web version of this text can be found at https://umsystem.pressbooks.pub/alpt1865/. This anthology of American Literatures Prior to 1865, is organized chronologically into four units, focusing on Colonial Literature, Literature of Native American Perspectives and Discovery, Literature of Nineteenth Century Reform, and Literature of the New Nation. It includes introductions to the many authors included to enhance the reader's contextual understanding of the chosen texts. This anthology is essential reading for any student or scholar of Early American literature.